EFFECT OF TEMPERATURE ON DIELECTRIC, FERROELECTRIC, AND PIEZOELECTRIC PROPERTIES OF KNLNS-BNKZ CERAMICS - Phan Dinh Gio; Bui Thi Tuyet Nhung (Tạp chí Khoa học Đại học Đà Lạt)
Traditional ceramic technology combined with a two-step sintering technique has been applied to prepare 0.96(K0.48Na0.48Li0.04)(Nb0.95Sb0.05)O3-0.04Bi0.5(Na0.82K0.18)0.5ZrO3 (KNLNS-BNKZ) piezoelectric ceramics. The experimental results show that the ceramic samples have a pure perovskite structure with the coexistence of tetragonal and rhombohedral phases. Effects of temperature on the dielectric, ferroelectric, and piezoelectric properties of the ceramics were investigated in detail. The results show that the characteristic parameters for the piezoelectric and ferroelectric properties of the ceramics, such as the electromechanical coupling coefficient kp, the piezoelectric factor d31, and the remnant polarization Pr are largely stable from room temperature to 100 °C.